Exploration of Students' Mathematical Literacy Abilities in Visualizing Division of Fraction - Indahwati, Rohmah; Sari, Dwi Rosita; Basri, Hasan (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research was to find out how prospective mathematics teachers can visualize the form of fractional division operations based on mathematical literacy skills. This research includes qualitative research with descriptive methods. This study was conducted on 3 students of the 3rd semester mathematics education program with high, medium and low mathematical ability with good communication skills. Researchers gave three questions on literacy tests. The tests given include problems related to division of integers by fractions, division of fractional numbers by integers and division of fractional numbers by fractional numbers. From the test results obtained, interviews were conducted of all three subjects. The results showed that all three subjects were able to understand and translate the questions and formulate what was asked of the questions. However all three subjects encountered constraints when trying to visualize the form of division of fractions by fractional numbers. They just memorize division formulas like “multiplying and inverting”. From the results of the data analysis, it can be concluded that the literacy ability of the subject in visualizing the form of the division operation is still classified as low.Keywords : Mathematical Literacy, Visualizing, Divison of Fraction.